Prevalence, Context, and Reporting of Drug-Facilitated Sexual Assault on Campus of Two Large Public Universities in the United States, 2005-2006 - Krebs, Christopher P. ([Verlag nicht ermittelbar], 2011)
The primary research objective of this study was to examine the prevalence, nature, and reporting of various types of sexual assault experienced by university students in an effort to inform the development of targeted intervention strategies. In addition, the study had two service-oriented objectives: (1) to educate students about various types of sexual assault, how they can maximize their safety, and what they can do if they or someone they know has been victimized and (2) to provide students with information about the campus and community resources that are available should they need assistance or have any concerns or questions. The study involved a Web-based survey of random samples of undergraduate students at two large public universities, one located in the South (University 1) and one located in the Midwest (University 2). Researchers drew random samples of students aged 18-25 and enrolled at least three-quarters' time at each university to participate in the study. The survey was administered in the winter of 2005-2006, and a total of 5,446 undergraduate women and 1,375 undergraduate men participated for a grand total of 6,821 respondents. Sampled students were sent an initial recruitment e-mail that described the study, provided a unique study ID number, and included a hyperlink to the study Web site. During each of the following weeks, students who had not completed the survey were sent follow-up e-mails and a hard-copy letter encouraging them to participate. The survey was administered anonymously and was designed to be completed in an average of 15 minutes. Respondents were provided with a survey completion code that, when entered with their study ID number at a separate Web site, enabled them to obtain a $10 Amazon.com gift certificate. The survey was divided into six modules. The Background Information module included survey items on demographics, school classification (year of study, year of enrollment, transfer status), residential characteristics, academic performance, and school involvement. An Alcohol and Other Drug Use module generated a number of measures of alcohol and drug use, and related substance use behaviors. A Dating module included items on sexual orientation, dating, consensual sexual activity, and dating violence. The Experiences module was developed after extensive reviews of past surveys of sexual assault and generated information on physically forced sexual assault and incapacitated sexual assault. For both physically forced and incapacitated sexual assault, information was collected on completed and attempted assaults experienced before entering college and since entering college. For male respondents, a Behaviors module asking about the perpetration of the same types of sexual assault covered in the Experiences module was included. The final module of the survey covered attitudes about sexual assault and attitudes about the survey. The data file contains 747 variables.